Exploring moral competence regression: a narrative approach in medical ethics education for medical students - Zielina, Martin; Škoda, Jaromír; Ivanová, Kateřina; Dostál, Daniel; Juríčková, Lubica; Anthony Procházka, David; Straka, Barbora; Doležal, Adam (BMC medical ethics, 2024)
BACKGROUND: Studies from different countries report a stagnation or regression of moral competence in medical students between the first and the last year of their studies, and the value of various educational interventions remains uncertain. METHODS: We used Moral Competence Test (MCT) to measure C-scores of moral competence to determine the change in the MCT C-scores between the first- and the fifth-year medical students from two medical schools in the Czech Republic in the academic year 2022/2023 and to analyze factors associated with the C-scores (observational study). In addition, for the first-year students, we compared the results of the MCT before and after an intervention in medical ethics curriculum (interventional study). We used a cross-sectional and descriptive design for the observational study. Students completed the MCT, consisting of two moral dilemmas (Worker´s Dilemma and Doctor´s Dilemma), the results measured by the C-score, which represents moral competence. RESULTS: In total, 685 students participated in the observational study. Objective 1: based on the analysis of the C-score, we observed a decrease in moral competence between the first and the fifth-year medical students (p < .001). Objective 2: we did not observe a statistically significant effect of gender (p = .278), or self-rated religiosity (p = .163). Objective 3: in the interventional study, 440 students participated in the pretest and 422 students participated in the posttest. The test of statistical significance found no improvement in students' moral competence after the intervention (p = .253). CONCLUSION: Medical students show a regression in moral competence during medical education; it was lower in medical students in their fifth year, compared to the first-year medical students without the effect of gender, or self-rated religiosity. Although educational intervention consisting of multiple tools of medical ethics teaching (PBL, CBL, KMDD and StorED) did not lead to increase in moral competence, the longitudinal effect of such intervention remains to be seen.
Keywords: dospělí; Medical students; Female; Case-based learning; Adult; mladý dospělý; ženské pohlaví; průřezové studie; lékařská etika; Problem-based learnig; Narration; lidé; Konstanz Method of Dilemma Discussion; Students, Medical; vyprávění; Curriculum; studenti lékařství; Cross-Sectional Studies; Moral competence; Male; Czech Republic; Education, Medical, Undergraduate; Young Adult; Narrative approach; mravy; Česká republika; Morals; kurikulum; Ethics, Medical; mužské pohlaví; studium lékařství pregraduální; Humans